2022
DOI: 10.1038/s41598-022-06956-4
|View full text |Cite
|
Sign up to set email alerts
|

Untargeted sequencing of circulating microRNAs in a healthy and diseased older population

Abstract: We performed untargeted profiling of circulating microRNAs (miRNAs) in a well characterized cohort of older adults to verify associations of health and disease-related biomarkers with systemic miRNA expression. Differential expression analysis revealed 30 miRNAs that significantly differed between healthy active, healthy sedentary and sedentary cardiovascular risk patients. Increased expression of miRNAs miR-193b-5p, miR-122-5p, miR-885-3p, miR-193a-5p, miR-34a-5p, miR-505-3p, miR-194-5p, miR-27b-3p, miR-885-5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 66 publications
0
5
0
Order By: Relevance
“…Although previous studies have reported associations of the identified miRNAs with impaired glucose metabolism, lipid metabolism, and cardiac dysfunction, the plasma miRNA signatures of CVD risk factors have not been fully elucidated at a population level in middle‐age or older individuals. 17 , 51 , 63 , 65 , 66 , 67 To that end, we elucidated miRNA signatures of CVD risk factors and replicated a subset of these miRNAs in an independent population‐based cohort study. We identified 6 miRNAs (miR‐193b‐3p, miR‐122‐5p, miR‐365a‐3p, miR‐194‐5p, miR‐192‐5p, and miR‐193a‐5p) that were associated with 5 or more CVD risk factors in the FHS.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Although previous studies have reported associations of the identified miRNAs with impaired glucose metabolism, lipid metabolism, and cardiac dysfunction, the plasma miRNA signatures of CVD risk factors have not been fully elucidated at a population level in middle‐age or older individuals. 17 , 51 , 63 , 65 , 66 , 67 To that end, we elucidated miRNA signatures of CVD risk factors and replicated a subset of these miRNAs in an independent population‐based cohort study. We identified 6 miRNAs (miR‐193b‐3p, miR‐122‐5p, miR‐365a‐3p, miR‐194‐5p, miR‐192‐5p, and miR‐193a‐5p) that were associated with 5 or more CVD risk factors in the FHS.…”
Section: Discussionmentioning
confidence: 96%
“…conducted untargeted sequencing of miRNAs from serum in 158 older participants who were healthy or had disease, revealing 30 circulating miRNAs associated with cardiovascular health and physical activity or disease. 51 Mens et al. identified 22 plasma miRNAs associated with at least 1 cardiometabolic trait and further reported 4 miRNAs to be strongly linked to lipid traits following multiomic analysis.…”
mentioning
confidence: 99%
“…None of the plasma miRs described by Estebanez et al matched with our 15 significantly changed miRs in exosomes from patient derived myotubes ( Estebanez et al, 2021 ). MiR-92b-5p might also be interesting, since it recently showed higher expression in healthy active individuals than in sedentary individuals ( Streese et al, 2022 ), indicating a role in physical activity/exercise. MiR-1233-5p was the miR most changed by EPS in our study, and the highly predicted target protein S100A7 was the protein most reduced after EPS.…”
Section: Discussionmentioning
confidence: 99%
“…Regulating neuronal cell injury [54] Serum biomarker for AD [55] Upregulated in AD [56] Associated with higher metabolic risk profile in older subjects [57] hsa-miR-199a-5p…”
Section: Hsa-mir-885-5pmentioning
confidence: 99%
“…Association with WML and cognitive impairment [16] Associated with higher metabolic risk profile in older subjects [57] Downregulated in blood of AD patients [62] Inhibit apoptosis of hippocampal neurons [63] hsa-miR-140-5p…”
Section: Hsa-mir-885-5pmentioning
confidence: 99%